Internal door closing habits in domestic premises: Results of a survey and the potential implications on fire safety. (December 2019) - Hopkin, Charlie; Spearpoint, Michael; Wang, Yong
Highlights: 45–60% probability internal doors are closed while sleeping (all respondents). Property type, presence of children and pets influence door closing habits. Respondents in apartments more likely to close bedroom doors. Respondents with pets and children typically more likely to leave doors open. Results suggest daily activities prioritised over safety benefits of closing doors. Abstract: It is generally accepted that keeping doors closed provides a means of protection by limiting smoke and fire spread. In the design of domestic buildings, it is therefore often assumed that occupants maintain a habit of keeping internal doors closed. The paper presents the results of an online survey to determine respondents' internal door closing habits for their domestic premises. This attracted 304 responses (250 of which were from the UK) and was then followed by a more detailed survey, attracting 26 replies, to elaborate on respondents' rationale behind their habits. The findings indicate that the overall probability that a kitchen, living room and bedroom door are closed while occupants are sleeping is 46%, 45% and 60%, respectively. It was found that the type of property, and whether respondents have children or pets, all have an influence on door closing habits. Respondents who lived in apartments were found to be up to 27% less likely to close kitchen or living room doors but more likely to close bedroom doors before going to sleep (+19%). In all instances, respondents with pets were typically more likely to keep doors open (ranging from 0% difference to +16%). However, when considering door closing behaviours for pet owners independent of the property type, it was found there was no statistically significant difference for bedroom door closing habits when sleeping. The analyses in this paper ultimately point towards the potential for daily household activities to take priority over the safety benefits which internal doors can provide.